Impacts on human health and environment related to the use of pesticides: An integrative review (Research, Society and Development, 2021)
Studies have shown a growing increase in the use of pesticides in conventional agriculture in Brazil and worldwide, leading to greater exposure of rural producers, consumers and the environment. With this in concern, an integrative review on the topic was carried out in the databases of the Web of Science and Scientific Electronic Library (SciELO) andLatin American and Caribbean Literature on Health Sciences (LILACS), published in Portuguese and English, between the years of 2015 and 2020, which addressed the theme of 'pesticides'. The forums included 35 publications that demonstrate the impacts on human health and on the environment related to the use of pesticides. Of the articles that were analyzed, 89% were related to pesticides and effects on human health, while only 11% referred to impacts on the environment. It was noted that there are important contributions of the consulted literature, mainly in dealing with the relationship of agrotoxicity with health and, on the other hand, there is evidence of incipient research aimed at the environment.